Features of Formation and Development of Innovation Centers Generate - Kulikova, Natalia N.; Kolomyts, Oksana N.; Litvinenko, Inna L.; Gurieva, Lira K.; Kamberdiyeva, Svetlana S. (International Journal of Economics and Financial Issues, 2016)
Russia entered the new millennium with the hope to build an updated state with a competitive economy. Today, competitive advantage is determined by either the size of the country, nor the level of reserves of natural resources, or even the power of financial capital. It is obvious that in the coming years will thrive on those States that provide the most complete manifestation of the professional skills and talents of its citizens will be able to excel in the development of new knowledge and practical achievements, transforming them into the most advanced technologies and products. For this is supposed to use market mechanisms to ensure a quick update, implementation and wide dissemination of advanced technologies, increasing production of competitive products in the world market. The basis of structural changes is the state innovation strategy and an active scientific and technical policy of firms and regions, focused on promoting the development of advanced research and technology breakthroughs. Scientific and technical progress affects the scope and structure of production has a significant impact on the entire world economy. Keywords: Innovation, innovative development JEL Classifications: Ðž31, O33, P14